Beliefs, Knowledge, and Perception of Indonesian Mental Healthcare Workers Regarding Mental Illness: A Cross-Sectional Study - Marthoenis Marthoenis (Wolters Kluwer Medknow Publications, 2024)
Background: The actions of healthcare workers in treating and caring for people with mental illness are influenced by various factors. Therefore, this study aimed to assess beliefs, knowledge, and perception of Indonesian Mental Healthcare Workers (MHWs) regarding mental illness. Materials and Methods: A cross-sectional study was conducted among 173 MHWs in May 2021 using a newly developed questionnaire distributed through convenience sampling methods. Results: Most respondents were female (n = 135, 77.14%) and married (n = 148, 84.57%), with a mean (SD) of age of 37.57 (6.55) years old. Most believed that mental illness was caused by personal weakness (n = 131, 74.86%) and often led to mental retardation (n = 115, 65.71%). Furthermore, approximately half of this population believed mental illness could be cured through marriage (n = 80, 45.71%). Conclusions: The evaluated MHWs commonly held misconceptions about the cause and treatments of mental illness. Consequently, relevant training was recommended to be performed for mental health literacy enhancement.